Body size and composition, physical activity and sedentary time in relation to endogenous hormones in premenopausal and postmenopausal women: Findings from the UK Biobank. Issue 8 (24th April 2020) - Tin Tin, Sandar; Reeves, Gillian K.; Key, Timothy J.
Abstract: Anthropometric and lifestyle factors may influence cancer risks through hormonal changes. We investigated cross‐sectional associations between body size and composition, physical activity and sedentary time and serum concentrations of oestradiol (premenopausal women only), testosterone, sex hormone binding globulin (SHBG) and insulin‐like growth factor‐I (IGF‐I) in 20 758 premenopausal and 71 101 postmenopausal women in UK Biobank. In premenopausal women, higher BMI (body mass index) was associated with a lower concentration of total oestradiol (15% difference in the highest vs lowest BMI group) and a higher concentration of calculated free oestradiol (22%). In both premenopausal and postmenopausal women, higher BMI was associated with higher concentrations of total and calculated free testosterone (premenopausal 29% and 113%, postmenopausal 39% and 126%, respectively) and lower concentrations of SHBG and IGF‐I (premenopausal 51% and 14%, postmenopausal 51% and 12%, respectively). Similar associations were observed with waist to height ratio, waist to hip ratio and body or trunk fat mass. Self‐reported physical activity was associated with somewhat lower concentrations of total and calculated free testosterone (premenopausal 10% difference [free testosterone], postmenopausal 5% and 11% difference respectively in the most vs least active group) and a higher concentration of SHBG (premenopausal 11%, postmenopausal 10%), and the opposite was true for self‐reported sedentary time. The associations were slightly stronger with accelerometer‐measured physical activity, but were attenuated after adjustment for BMI. Overall, our study confirms strong associations of hormones and SHBG with anthropometric factors. The associations with physical activity and sedentary time were at most modest. Abstract : What's new? Circulating concentrations of oestrogen and androgen hormones are associated with increased risk of breast and some gynaecological cancers in women. These same cancer types are also influenced by obesity and possibly physical activity, though whether the impacts of the latter factors are mediated by hormones remains uncertain. In this investigation of endogenous hormones, body composition, physical activity, and sedentary time in pre‐ and post‐menopausal women, strong associations were found between adult anthropometric factors, hormones, and sex hormone binding globulin. Associations were modest for physical activity and sedentary time. The findings support the hypothesis that sex hormones mediate the impacts of anthropometric factors on risk for some cancers in women, but suggest that the possible protective effects of physical activity against cancer might be mediated by pathways other than sex hormones.